Boundary‐Crossing Field Research Marks the Way to Evidence‐Based Management of Mercury in Forest Landscapes. Issue 8 (11th August 2022) - Bishop, Kevin; Eklöf, Karin
Abstract: The atmospheric deposition of long‐range atmospheric mercury pollution presents forest managers with a "wicked" problem—forestry operations run the risk of mobilizing this pollution legacy. Management of that risk would benefit from a process‐based understanding of how forest management influences the mercury cycle. This commentary highlights the value for building such an understanding of a comprehensive Before‐After‐Control‐Impact study reported by McCarter et al. (2022), https://doi.org/10.1029/2022JG006826 on the Marcel Experimental Forest in the north‐central continental US. That study looked at how different types of forest harvest influenced the movement of mercury through the landscape. The results of this study place it at the minimal end of the range of impacts on Hg mobilization resulting from forest harvest. What makes this paper, together with the companion papers resulting from this study, particularly valuable for improving the understanding of forestry influences on mercury is the number of system boundaries that the study crossed: between land and atmosphere, from a forested hillslope down into a wetland, and finally up into the biota on that wetland. Plain Language Summary: Forest harvest can mobilize toxic mercury from forest soils and move it into living organisms. This mercury originated in air pollution created far away from the forest, but forest managers still need to deal with the risks of this "pollution legacy" to people, fish and wildlife. A recent study in the north‐central US took a detailed look at how two different types of forest harvest mobilized mercury in the soil. This study showed a relatively small impact of the forest harvest on mercury relative to some other studies. Since previous studies have found a wide range of mercury responses to forest harvest, this carefully designed and executed study has value in adding to the evidence base about forest management impacts on mercury in the environment. What is particularly valuable about this study is its comprehensiveness, since it crosses a number of environmental system boundaries: between the forest and the atmosphere, from upslope mineral soils into a downslope peatland, and from the wetland environment into the biota. Key Points: A well‐executed study sheds new light on the "wicked" problem of how forest harvest influences the mobility and bioaccumulation of mercury The study is particularly valuable because it extends across several environmental system boundaries: atmosphere‐forest‐peatland‐biota Crossing downstream boundaries can show how more of the stream network embedded in a landscape reacts to land‐use and climate change